University Course Timetabling with Genetic Algorithm: A Case Study - Toha Ardi Nugraha; Karisma Trinanda Putra; Nur Hayati (Journal of Electrical Technology UMY, 2017)
University Course Timetabling Problems is a scheduling problem to allocate some lectures with some constraint, such as the availability of lecturers, number of classrooms and time slot in each day. The schedule of courses is one of important factors before start the semester in order to manage the study process. Generally, the university course scheduling in some universities are usually created manually through administration office. It needs to synchronize for all schedules from all departments in faculty of the university. In addition, the limitations of classroom and timeslot can make collision of the courses, lecturers and also incompatibility between the room capacity and the number of students whom take the course in the class. This paper proposes the university course time tabling systems. Based on some simulations with 93 courses, 18 lecturers and up to six classrooms, the result is that the system will get the best violation if the system adds more number of iteration. This situation also happens in the result of the scheduling lectures, the system will get the best percentage when the number of iteration sets as maximum.